Learning Journal and the Studentsâ Achievement in Grammar Class: Transitivity Analysis (Dinamika Ilmu, 2017)
Learning journal enables students to reflect of what they have experienced in the learning process. This article presents the studentsâ learning journal in grammar class. For some students, grammar is seen as a course which does not attract their interest. It resulted on their ignorance of the course. However, students have to face the fact that grammar is an integral part of their literacy as it affects the meaning of their utterances, both spoken and written. The participants involved were the 37 students of English Letters Department, Sanata Dharma University. The students were in Structure IV course, one of grammar classes offered by the study program. The instruments involved were the studentsâ learning journal wrtten during the semester and their final grades. The learning journal was analyzed by means of Hallidayâs transitivity. The findings reveal that most of the students used material process in their learning journal, while mental and relational processes do not appear often in the journal. The studentsâ achievement in class is dominated by an A in the end of the semester. Relating the two findings above, this article concludes that studentsâ practice of their knowledge in their social life affects their achievement in class. Â The employment of material process in the studentsâ learning journal reveals the studentsâ practice and purpose of learning grammar.Â Â Keywords: Â Â Â  learning journal, grammar, transitivity